Implementation of Image Processing in Matlab for Prediagnosis in Ophthalmology (LACCEI, 2024)
This research seeks to explain the implementation of image processing in Matlab and its relationship with the prediagnosis of eye problems as a basis for automating the process of medical image analysis in this field. The pandemic has generated a worldwide health crisis, but in our country a significant impact on the outcome of teleconsultations has been observed, since the challenge lies in the lack of clarity when visualizing the patient's eye through a screen. Therefore, we propose the application of a single-person booth that will allow real-time capture of the patient's eye and its respective analysis. In addition, to avoid contact, an infrared sensor was implemented to detect the entry of people into the booth. Finally, the processing techniques give us a clear picture and demonstrate that the project can be adapted to specific situations with the knowledge of mechatronic and biomedical engineering.